2014
DOI: 10.4066/amj.2014.2094
|View full text |Cite
|
Sign up to set email alerts
|

A study of acute otitis externa at Wellington Hospital, 2007–2011

Abstract: Pseudomonas aeruginosa is the most common microbe causing acute otitis externa in patients that require hospital level management in Wellington, New Zealand. In most cases, patients received appropriate topical therapy; however, it appears a large number received systemic antibiotic therapy without topical treatment. We recommend broad-spectrum topical antimicrobial therapy in all patients with uncomplicated AOE and culture-sensitive topical treatment with consideration of systemic antimicrobials for severe AO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…A five-year retrospective study from New Zealand (2007)(2008)(2009)(2010)(2011), with recorded data of 347 patients with otitis externa from Wellington Hospital, showed that P. aeruginosa was the most common organism (46.5%), while S. aureus was the second most common (31.9%) [3]. Most studies published during the last 10-years from various countries reported that microbial otitis externa is frequently caused by P. aeruginosa and less frequently by other Gram-negative bacteria and S. aureus and fungi [3,5,9,20]. Two old Jordanian studies have reported the spectrum of organisms isolated from a general ear infection as follows.…”
Section: Discussionmentioning
confidence: 99%
“…A five-year retrospective study from New Zealand (2007)(2008)(2009)(2010)(2011), with recorded data of 347 patients with otitis externa from Wellington Hospital, showed that P. aeruginosa was the most common organism (46.5%), while S. aureus was the second most common (31.9%) [3]. Most studies published during the last 10-years from various countries reported that microbial otitis externa is frequently caused by P. aeruginosa and less frequently by other Gram-negative bacteria and S. aureus and fungi [3,5,9,20]. Two old Jordanian studies have reported the spectrum of organisms isolated from a general ear infection as follows.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, S. aureus and P. aeruginosa were the main agents of EO [ 5 , 27 ]. EAC mycoses had lower incidence (approx.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, EO is due to bacterial infection, but less frequently it is caused by fungi or it is associated to local or systemic non-infectious processes [ 2 , 3 , 4 ]. Staphylococus aureus ( S. aureus ) and Pseudomonas aeruginosa ( P. aeruginosa ) are the main etiological agents of the disease, but other Gram-negative bacteria, such as Escherichia coli ( E. coli ) and Klebsiella spp., can be involved [ 1 , 5 ]. The exposition of EAC to water, humidity, local traumatism, occlusion, or the occurrence of dermatitis can increase the susceptibility to infections.…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 3 S. aureus is thought to be the second most common pathogen in acute bacterial otitis externa, with case series identifying S. aureus in up to 40% of cases. 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 Studies from Pakistan, Korea and New Zealand found rates of S. aureus AOE above 30%, 10 , 11 , 12 while the most recent study in the U.S. reported rates of 7.8%. 3 …”
Section: Introductionmentioning
confidence: 99%